Protecting Forests From Conversion: The Essential Role of Supply-Side National Laws - Haywood, Caroline; Henriot, Clotilde (Frontiers in Forests and Global Change, 2019)
• The growing demand in global markets for commodities like palm oil, soy and cocoa has a disastrous impact on forests, carbon emissions, as well as the lands and livelihoods of forest-dependent people. • Governments, private sector, civil society and forest-dependent people have, separately or jointly, committed to voluntary actions to protect forests (e.g. pledges, zero deforestation commitments, certification standards). • However, recent research shows that these voluntary commitments and standards have neither halted nor slowed deforestation. This demonstrates that they cannot stand alone. • Alongside voluntary action, national legal frameworks that regulate forest conversion are crucial. This research explores the importance of supply-chain laws for reducing deforestation from forest-risk commodities and the legal options available to address competing demands for forested lands.